Pengolahan Hasil Perkebunan Kelapa sebagai Peningkat Ekonomi Masyarakat Desa Patuk Kecamatan Patuk Kabupaten Gunungkidul - Binarti, Floriberta (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Patuk Village is one of the villages located in Patuk District, Gunungkidul Regency, Special Region of Yogyakarta. With KKN 81 Society 5.0 activities in this village, namely increasing the potential of village natural resources, namely garden land that is not cultivated into coconut plantations and coconut processing into coconut oil. The author took the initiative to provide insight by providing how to make coconut oil. Based on the data collection regarding the potential of Patuk Village, the authors produced outputs in the form of e-books and video pocket books on how to process coconuts, e-books and videos about village potential. Authors expect that these results can be useful and become a business opportunity for Patuk Village that can increase the economy of the Patuk Village community.